Seaweed Dodol Of Aulia Sari Small Medium Enterprise Product Quality Improvement Using Kano Model And Product Quality Dimension Integration - Aziz Pratama Thahir; Yati Rohayati; Aulia Fashanah Hadining (eProceedings of Engineering, 2015)
Abs tract Aulia Sari is the only bus ines s entity that produces s eaweed dodol in Java is land. Dodol s ales number in Wes t Java is quite high becaus e it is one of the typical s ouvenirs of Wes t Java. Seaweed dodol Aulia Sari with many benefits offered from s eaweed, did not get a big s elling number in Bandung as the city where the bus ines s entity is es tablis hed. This res earch is intended to improve the product quality of s eaweed dodol to increas e cus tomer s atis faction level us ing integration of Kano method and Product Quality dimens ion. Advantages of us ing Kano and dimens ions of product quality in product developme nt has been proven in s everal previous s tudies to improve the product performance. This s tudy us es 4 product quality dimens ions that have been adapte d to the product in the form of food and 22 variable of products quality derived from the Voice of the Cus tomer and integrated with Kano method. The purpos e of this s tudy is to get what factors are going to be maintai ne d, improve d or removed from s eaweed dodol products of Aulia Sari SME. Keywor d: kano, product quality, UKM.